Antagonizing Il10 and Il4 signaling via intracerebral decoy receptor expression attenuates Aβ accumulation - Emily J. Koller; Karen N. McFarland; Conner Angelle; John Howard; Danny Ryu; Kristy D. Dillon; Aya Erquizi; Mihir Beheray; Elsa Gonzalez De La Cruz; Pedro E. Cruz; Jada Lewis; Todd E. Golde; et al. (Acta Neuropathologica Communications)
Abstract Multiple lines of evidence indicate that immune signaling can impact the pathological progression in Alzheimer’s disease (AD), including amyloid deposition, tau aggregation, synaptic pathology and neurodegenerative trajectory. In earlier studies, we reported that intracerebral expression of the anti-inflammatory cytokines, Interleukin-10 (Il10) and Interleukin-4 (Il4), increased amyloid β (Aβ) burden in TgCRND8 mice, a preclinical model of AD-type amyloidosis. As both Interleukin-10 receptor (IL10R) and Interleukin-4 receptor (IL4R) are upregulated in an age-progressive manner in rodent models of AD and in specific regions of human AD brains, we hypothesized that a decoy receptor strategy specifically targeting Il10 and Il4 signaling could have a disease-modifying effect. We derivatized the ectodomains of mouse Il10R (sIl10R) and mouse Il4R (sIl4R) into corresponding recombinant solubilized receptor forms and delivered these intracranially into neonatal TgCRND8 mice or hippocampally into adult TgCRND8 mice with pre-existing Aβ deposits. AAV-mediated expression of sIl10R and sIl4R robustly attenuated Aβ burden in TgCRND8 mice when expressed neonatally while in the hippocampus injection cohort, AAV-sIl4R, but not sIl10R, reduced Aβ burden. sIl10R and sIl4R had opposing effects on microglial and astrocyte proliferation, with sIl10R generally reducing gliosis. RNAseq analysis showed that sIl10R likely acts as a microglial immune checkpoint inhibitor while both sIl10R and sIl4R expression show unexpected impacts on genes related to circadian rhythm. Notably, neither Il10 nor sIl10R expression altered tau pathology in two tau transgenic models, despite robust expression and impacts on glial proliferation. Together, these data reveal that decoy receptor mediated targeting of physiological Il10 or Il4 signaling can beneficially impact amyloid deposition and thus represent novel immunomodulatory approaches for AD therapy.